Efeito imunomodulador da vitamina D e silibinina sobre subpopulações de células T CD4+ em gestantes portadoras de pré-eclâmpsia - Ribeiro, Vanessa Rocha [UNESP] (2021)
Vitamin D (VD) is a multifunctional prohormone and low VD status in pregnancy may contribute to the risk of adverse perinatal outcomes, such as preeclampsia (PE). This molecule may modulate the polarization of T cell subsets during gestation. This study evaluated the in vitro immunomodulatory effect of VD on the gene expression of transcription factors and on cytokine production by T cell subsets. Twenty pregnant women with PE and twenty normotensive (NT) pregnant women were studied. Plasma concentration of VD, 25(OH)D3, was evaluated by chemiluminescence. PBMCs from preeclamptic and NT pregnant women were cultured in the absence or presence of VD to determine gene expression of T-bet (Th1), GATA-3 (Th2), RORγt, and Runx1 (Th17), FoxP3 (regulatory T cell- Treg), and the receptors of VD (VDR) and IL-23 (IL-23R) by quantitative PCR. The concentration of cytokines in the PBMC supernatant culture was determined by cytometric bead array and ELISA immunoassay. The results showed that plasmatic levels of VD were significantly lower in the PE group. The treatment of PBMCs from preeclamptic women with VD induced downregulation of genes related to inflammatory profiles (Th1 and Th17), as well as an increase of anti-inflammatory and regulatory profiles (Th2 and Treg). Thus, VD treatment decreased the release of TNF-α, IL-17, IL-6, and IL-23 while it increased the levels of IL-10 in the PE group. VD induces an immunomodulatory effect in T cell subsets from pregnant women with PE, polarizing these cells to an anti-inflammatory and regulatory profile